Governance structures and sustainability in Indian Ocean sea cucumber fisheries. (June 2015) - Eriksson, Hampus; Conand, Chantal; Lovatelli, Alessandro; Muthiga, Nyawira A.; Purcell, Steven W.
Abstract: Good governance is paramount to the sustainability of fisheries, and inclusiveness of stakeholder groups has become the centerpiece in the ethos of managing small-scale fisheries. Understanding the effect of governance network structures on fishery sustainability can help guide governance to achieve desired outcomes. Data on resource users, fishing methods, governance networks and classifications of stock health were compiled for 17 sea cucumber fisheries in the Indian Ocean. The subjective influence of the actors and the complexity of governance networks on the health of wild stocks were analyzed. The fisheries differed widely in their resource users, fishing methods and governance networks. Little correspondence was found between the number of nodes in the governance networks and the health (exploitation status) of wild stocks. Government entities dominated the networks but neither their relative influence in the networks nor their proportionate contribution to the number of entities in the networks greatly affected stock health. These findings do not refute the benefits of inclusive governance, but rather suggest that multiple other factors (e.g. inadequate regulations, weak enforcement, high number of fishers) are also likely to play a role in influencing sea cucumber fishery sustainability. These factors must be tackled in tandem with good governance. Highlights: Sea cucumber fisher types and fishing methods varied between countries. Number of governance nodes was unrelated to fishery sustainability. Multiple factors other than governance network influence sustainability. Deeper insight into governance attributes and functioning is required. Governance network analysis was a useful tool to visualize structure.